On the Renovation of Religious Discourse: Analysis of Concepts, and Internal and External Disciplines - Housamedden Darwish (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
This article aims to clarify the meaning of “renovation of religious discourse”, specifically by defining the disciplines of this renovation and their importance in determining its meaning. The disciplines play a pivotal role in determining the nature, meaning, and possibilities of renovating religious discourse. To demonstrate this thesis, the article will first make some conceptual distinctions between ‘discourse of religion’ and ‘religious discourse’, between ‘religion’ and ‘religiosity’, between ‘renovation in religious discourse’ and ‘renovation of religious discourse’. Secondly, it will make a distinction between internal and external disciplines. Internal disciplines lie within the religious text itself and in the hermeneutic circle between understanding parts of the text and understanding it as a whole, between understanding and pre-understanding, between the inside and the outside. In doing so, the paper focuses mainly on the role of the ruling political and economic powers and authorities. The paper concludes that renovating religious discourse is a political and institutional issue rather than a purely religious one related to individuals and that it is conditional on the state and its political system, the extent of its actual adoption of the concepts of ‘the state of citizenship and law’, democracy, and the extent to which it protects freedoms, differences, and pluralism.